2001
DOI: 10.1159/000053923
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Sonographic Formulas for Estimating Fetal Weight below 1,250 g: A Series of 119 Cases

Abstract: Objective: The aim of this study was to determine the accuracy of sonographic methods for estimating fetal weight <1,250 g on the basis of ten published formulas falling into two principal categories: general formulas applied to all fetuses, and formulas specifically developed for very-low-weight fetuses. Methods: Recent biometric data (obtained less than 7 days before birth) on 119 fetuses weighing <1,250 g were used retrospectively. Estimated fetal weights derived from ten published formulas were compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 19 publications
1
32
0
1
Order By: Relevance
“…Seventeen studies tried to evaluate the best formula for FWE [6,7,9,11,12,13,14,15,16,17,18,19,20,21,22,23,24] (table 4). The most frequently examined formulas are those of Hadlock, which were compared to other formulas in all studies listed above, except in the study by Mills et al [9] who only compared two formulas (Shepard and Warsof).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen studies tried to evaluate the best formula for FWE [6,7,9,11,12,13,14,15,16,17,18,19,20,21,22,23,24] (table 4). The most frequently examined formulas are those of Hadlock, which were compared to other formulas in all studies listed above, except in the study by Mills et al [9] who only compared two formulas (Shepard and Warsof).…”
Section: Resultsmentioning
confidence: 99%
“…The formulas of Campbell, Merz, Shepard and Warsof have been examined 7, 8, 12 and 8 times, respectively. Thirteen of the studies found one of the Hadlock formulas to be the most accurate [6,7,11,13,14,15,16,19,20,21,22,23,24]. All Hadlock formulas seem to be equally accurate, as Meyer et al [12] who compared five Hadlock formulas found no significant difference in systematic or random error.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While Barel et al [27] included EFW evaluations taken within 1 week of delivery, our study focused on EFW evaluations taken within 3 days of delivery, and in our cohort, most sonographic evaluations were performed even in a shorter interval; thus, it may minimize the error attributed to fetal growth within 1 week [28]. Other studies demonstrated a range of systematic error of 7-10% [29], 9-15% [30], 0-27.9% [5] and 8.5-37.6% [31]. However, this comparison is arguable due to methodological limitations attributed to relatively small sample sizes, differences in time interval from sonographic evaluation to delivery and different study populations (e.g.…”
Section: Discussionmentioning
confidence: 99%